Disaster Mitigation Policy by The Government Of Bima In Realizing A Disaster Resilient City - Firmanto, Taufik; Ridwan; Gufran; Andi, Andi (Universitas Muhammadiyah Surakarta, 2022)
The purpose of this research is to describe the local government policies in realizing Bima as a Disaster Resilient City and to describe the form of disaster mitigation policies by the Bima government in realizing a Disaster Resilient City. Research method of this research is normative-empirical legal research (Mix Methods), using a statutory approach (Statute Approach), and a conceptual approach, the type of data used is secondary data and is supported by primary data. The result shows that the disaster mitigation policy efforts developed by the Bima City government are in the form of Structural (Physical) Mitigation, drainage systems, retention dams, construction of retaining dams, making check dams, dams, earthquake-resistant house river embankments. Non-Structural (Non-Physical) Mitigation legislation, training, socialization. The policy forms of the Bima Government indicate that a Regional Regulation is made which includes the establishment of development policies that pose a risk of disaster, disaster prevention activities, emergency response and rehabilitation. In addition, other policies are 7 priority Regional Resilience Index (IKD) and 71 Regional Resilience Index Indicators in 2020/2021. The usefulness of this research is academically, this research is expected to be useful for further researchers as well as the development of legal science in the future, practically, this research is expected to be a reference for further researchers and the Government in particular in studying how disaster mitigation policy arrangements by Bima Government in order to realize Disaster Resilient City. The authenticity of this research lies in the regulation of disaster mitigation policies, as far as the authors search that the policies carried out by the City government already exist, but in the post-disaster period, those who have conducted research on other objects. Therefore, it is considered important to do research.